2020
DOI: 10.1088/1361-648x/abb1cd
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of crystal structure and magnetic properties of strontium substituted bismuth ferrite thin films

Abstract: Thin films of Bi(1−x)Sr x FeO3 (X = 0.00, 0.05, 0.10, 0.20, and 0.30) are synthesized on ultra-cleaned glass substrates by simple spray pyrolysis method at 550 °C. The crystal structures of the thin films are investigated by x-ray diffraction (XRD). The Rietveld refinement data for all the thin films are confirmed a single-phase ABO3 type of rhombohedral structure belonging to the R3c space group. The field emission scanning electron microscopy (FESEM) analysis reveals th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The major interest of this work is to observe the modifications in the magnetic properties of BFO after Ca substitution. In earlier work [20,21], we observe that Ba and Sr substitution affects the cycloidal antiferromagnetic structure of BFO and found that at 10% Ba doping BFO and 20% Sr doped BFO, the saturation magnetization, remanent magnetization and coercive field increases significantly. In order to get improvement in overall magnetic properties, we prepared different constituents of Ca doped BFO thin films.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…The major interest of this work is to observe the modifications in the magnetic properties of BFO after Ca substitution. In earlier work [20,21], we observe that Ba and Sr substitution affects the cycloidal antiferromagnetic structure of BFO and found that at 10% Ba doping BFO and 20% Sr doped BFO, the saturation magnetization, remanent magnetization and coercive field increases significantly. In order to get improvement in overall magnetic properties, we prepared different constituents of Ca doped BFO thin films.…”
Section: Resultsmentioning
confidence: 74%
“…Also, the volumic mass density decreases continuously with the addition of Ca amount which is responsible for the smaller atomic mass of Ca 2+ (40.07 amu) than that of Bi 3+ (208.98 amu). The degree of structural distortion can be visualized from the tolerance factor (t) of the prepared samples which is calculated similarly as our previous reports [20,21]. All the prepared samples possess R3c type hexagonal structure [37,38].…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations